Colostrum of healthy mothers contains broad spectrum of secretory IgA autoantibodies - Pribylova, Jaroslava; Krausova, Klara; Kocourkova, Ingrid; Rossmann, Pavel; Klimesova, Klara; Kverka, Miloslav; Tlaskalova-Hogenova, Helena (Journal of clinical immunology, 2012)
PURPOSE: Human colostrum and milk provide a newborn with immunomodulatory components, ensuring protection and proper development of the immune system. Secretory IgA antibodies in colostrum represent the first line of defence against harmful substances, but their potential spectra of reactivity with autoantigens remains unclear. Here, we characterised the repertoire of natural sectretory IgA autoantibodies in colostrum of healthy mothers. METHODS: The human colostrum samples from 39 healthy mothers were analyzed for autoantibodies by indirect immunofluorescence, dot blots, immunoblots and ELISA. RESULTS: We found that there is high diversity in reactivities of colostral IgA antibodies to autoantigens among individual samples. Using tissue sections and biochips commonly used for autoimmunity testing, we found that most samples reacted with monkey ovary (79.3%), monkey pancreatic tissue (78.6%), human HEp-2 cells (69%) and monkey adrenal gland (69.0%), fewer samples reacted with monkey liver tissue (47.2%), rat stomach (42.9%), monkey testicular tissue (41.4%), monkey salivary gland (39.3%), rat kidney (32.1%) and monkey cerebellar tissue (17.9%). At the protein level, we detected reactivity of IgA with 21 out of 25 (auto) antigens. The majority of the samples reacted with the pyruvate dehydrogenase complex, E3 ubiquitin ligase, cytosolic liver antigen, promyelocytic leukemia protein and nuclear pore glycoprotein-210. Using ELISA, we found reactivity of colostral IgA antibodies against examined extractable nuclear antigens, double stranded DNA, phospholipids and neutrophil cytoplasm. CONCLUSIONS: The broad spectrum of polyreactive natural autoantibodies present in human colostrum may contribute to proper development of mucosal immune system of the breastfed infant.
Keywords: Lactation; specificita protilátek; imunoglobulin A sekreční; Rats; Immunoglobulin A, Secretory; Colostrum; Protein Binding; těhotenství; kojenec; proteiny; mladiství; imunohistochemie; Autoantigens; Infant; Adult; Breast Feeding; krysa rodu Rattus; Immunohistochemistry; ženské pohlaví; ELISA; zvířata; Humans; Pregnancy; Haplorrhini; kojení; matky; Haplorhini; Mothers; autoprotilátky; autoantigeny; vazba proteinů; laktace; Antibody Specificity; kolostrum; Enzyme-Linked Immunosorbent Assay; dospělí; Female; Adolescent; Proteins; Autoantibodies; lidé; Animals